1995
DOI: 10.1007/bf00311257
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial plication combined with mitral valve surgery in patients with a giant left atrium

Abstract: The benefits of performing left atrial plication during mitral valve surgery for patients with a giant left atrium were evaluated by analyzing the short- and long-term surgical results and changes in the left atrial dimension (LAD) and respiratory function of 30 patients. Of the 30 patients, 2 (7%) died of multiple organ failure on postoperative days 26 and 117, but no other deaths occurred during the mean follow-up of 5.9 +/- 2.1 years. Valve thrombosis was observed in one patient and cerebral complications w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 6 publications
0
5
1
1
Order By: Relevance
“…They also reported that symptoms due to enlargement of the left atrium did not show any decrease in the follow-up. 24,26 In our study, the left atrial volumes of patients in Group 1 were significantly different between preoperative period and the 6th month (p < 0.001), whereas such a difference was not observed in Group 2 patients (p ¼ 0.158). In intragroup comparisons, we found no difference in left atrial volumes between the 6th and 12th months and the 12th and 18th months (p > 0.05).…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…They also reported that symptoms due to enlargement of the left atrium did not show any decrease in the follow-up. 24,26 In our study, the left atrial volumes of patients in Group 1 were significantly different between preoperative period and the 6th month (p < 0.001), whereas such a difference was not observed in Group 2 patients (p ¼ 0.158). In intragroup comparisons, we found no difference in left atrial volumes between the 6th and 12th months and the 12th and 18th months (p > 0.05).…”
Section: Discussioncontrasting
confidence: 49%
“…Hagihara et al 26 reported in another series of 30 patients that left atrial sizes of their patients decreased from 69.0 AE 8.5 to 53.7 AE 9.1 mm in the early stage, whereas no further decrease occurred within the next 5 years. They also reported that symptoms due to enlargement of the left atrium did not show any decrease in the follow-up.…”
Section: Discussionmentioning
confidence: 91%
“…However, this is difficult to understand when warfarin was in use. [16][17][18] In our follow-up, only one patient had a transient ischemic attack without any neurological sequela.…”
Section: Discussionmentioning
confidence: 70%
“…Our study found a decrease in LA size after 5 years of follow-up, while others have reported a reduction in LA size in the immediate postoperative period, but no further reduction during follow-up. 15,16 There were more postoperative events in the group with larger LA, but this was not significant. AF was similar in both groups during follow-up.…”
Section: Discussionmentioning
confidence: 82%